2017
DOI: 10.1159/000471235
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prenylated Proteins, Autophagy Impairment and Apoptosis in SH-SY5Y Neuronal Cell Model of Mevalonate Kinase Deficiency

Abstract: Background/Aims: Mevalonate Kinase Deficiency (MKD), is a hereditary disease due to mutations in mevalonate kinase gene (MVK). MKD has heterogeneous clinical phenotypes: the correlation between MVK mutations and MKD clinical phenotype is still to be fully elucidated. Deficiency of prenylated proteins has been hypothesized as possible MKD pathogenic mechanism. Based on this hypothesis and considering that neurologic impairment characterizes Mevalonic Aciduria (MA), the most severe form of MKD, we studied the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Moreover, induction of autophagy decreased the LPS-induced IL-1b release in PBMCs from healthy controls, whereas induction of autophagy had no significant effect on LPS-induced IL-1b release in PBMCs from MKD patients (79). In line with this, transient overexpression of MVK variants I268T and N301T in neuronal SH-SY5Y cells was found to increase cytosolic RhoA levels, impair autophagy and increase apoptosis (80). In another study, however, the transient expression of CAAX-deficient RhoA in THP-1 cells did not affect mitochondrial membrane potential and autophagy, although it resulted in mitochondrial elongation (58).…”
Section: Mitochondrial Dysfunction and Impaired Autophagy In Mkdmentioning
confidence: 67%
“…Moreover, induction of autophagy decreased the LPS-induced IL-1b release in PBMCs from healthy controls, whereas induction of autophagy had no significant effect on LPS-induced IL-1b release in PBMCs from MKD patients (79). In line with this, transient overexpression of MVK variants I268T and N301T in neuronal SH-SY5Y cells was found to increase cytosolic RhoA levels, impair autophagy and increase apoptosis (80). In another study, however, the transient expression of CAAX-deficient RhoA in THP-1 cells did not affect mitochondrial membrane potential and autophagy, although it resulted in mitochondrial elongation (58).…”
Section: Mitochondrial Dysfunction and Impaired Autophagy In Mkdmentioning
confidence: 67%
“…59 Impaired autolysosomal turnover and increased IL1B secretion have been observed in the context of MKD mutations, suggesting these pathways are critical in disease. 60,61 This observation suggests that lysosomal function directly affects intestinal homeostasis, potentially through an autophagy-dependent mechanism. Furthermore, recent studies have identified a role for GPR65, an H + -sensing G protein-coupled receptor, in maintaining lysosomal pH and thus lysosomal function.…”
Section: Lysosomal Dysfunction and Pathogenesismentioning
confidence: 99%
“…In addition, the increase in apoptosis following MVK interference was significantly attenuated by GGPP, whereas the overexpression of MVK significantly decreased the apoptotic rate of human keratinocytes. Autophagy impairment, apoptosis, and lack of prenylated proteins were observed in SH-SY5Y neuronal cell model of MVK deficiency (17). In addition, MVK mutation and deficiency were shown to cause a rare autosomal recessive disease called mevalonic aciduria.…”
Section: Discussionmentioning
confidence: 99%